Phytoestrogen metabolism by lactic acid bacteria: Enterolignan production by Lactobacillus salivarius and Lactobacillus gasseri strains. (October 2017) - Bravo, Daniel; Peirotén, Ángela; Álvarez, Inmaculada; Landete, José Mª
Highlights: Presence of enterolignans in plasma is protective against certain chronic diseases. Lb. salivarius INIA P183, Lb. salivarius INIA P448 and Lb. gasseri INIA P508 produce enterolignans. These strains have great biotechnological potential for the enterolignans production. Abstract: Phytoestrogens are plant polyphenols similar to human estrogens. Isoflavones, ellagitanins, and lignans are metabolized by intestinal bacteria into equol, urolithins, and enterolignans, respectively, which are more bioavailable and bioactive, having beneficial effects on health. In this paper, we analysed the production of equol, 5-hydroxy-equol, enterodiol and enterolactone by 70 strains of Lactobacillus, Lactococcus and Enterococcus . Enterodiol and enterolactone production was found in Lactobacillus salivarius INIA P183, Lb. salivarius INIA P448 and Lactobacillus gasseri INIA P508, in levels around 46 µM and 6 µM respectively. However, we did not find neither equol nor 5-hydroxy-equol producing strains. Furthermore, analysis of the ellagic acid metabolism was extended to a total of 138 lactic acid bacteria strains, although none of them produced urolithins. This is the first time that simultaneous production of enterolactone and enterodiol is described in bacteria with probiotic potential, open their possible application in functional foods.